Transitioning from junior to senior: a case study on elite judokas in South Korea - Hong, Hee Jung; Hong, Seung Han (Frontiers in Psychology, 2023)
This study explores the experiences of Korean elite judokas during their junior to senior transition (JST), including both male and female participants, to provide empirical evidence for the development of tailored support services or programs for this target population. We recruited 12 elite judokas for our study, comprising eight males and four females, all in their first year of university. Given their preferences and availability at the time of data collection, participants were divided into three focus groups: Focus Group 1 (FG1; four male participants), Focus Group 2 (FG2; four female participants), and Focus Group 3 (FG3; four male participants). Thematic analysis was applied to analyze the data from the focus group interviews. Five main themes were identified: (a) COVID-19-Induced Frustration, (b) From Big Fish in a Small Pond to Small Fish in a Big Pond, (c) Challenges in Academic Commitment, (d) Adapting to Transitions in Living Arrangements, and (e) Recognizing Support Needs for the JST. The findings of this study provide both theoretical and practical implications that could improve judokas' experiences during the challenging physical and mental phase of JST, as well as inform the establishment of tailored support programs and schemes for successful and smooth JSTs for athletes.